Analisis Faktor yang Berhubungan dengan Penggunaan Implan oleh Akseptor KB di Puskesmas Rawat Inap Sukabumi Kota Bandar Lampung - Marlina Marlina (Jurnal Kesehatan, 2017)
In quantity, the number of implant acceptors were belongs to a low category compared to non-implanted acceptors. The low acception of implanted KB by acceptor in the Work Area of Sukabumi Inpatient Health Centers was due to the emergence of many complaints, among them 65% experienced menstrual pattern changes and 21% said that fertility effect of implant was relatively long. This study was to know the factors which related to the using of Implan by KB acceptor in Sukabumi Inpatient Health Centers, Bandar Lampung, in 2016. This study was analytical survey design with case control plan and qualitative research. Population were women of childbearing age in Sukabumi Inpatient Health Centers Bandar Lampung, as much as 1.716 people. The sampling technique was using proportional random sampling. Qualitative data analytic were using the frequency distribution, chi-square and logistic regression. The result showed that there was relationships age (p=0,002), education (p=0,000), job (p=0,012), numbers of children (p=0,000), birth spacing (p=0,004), attitude (p=0,000), cost (p=0,016), health workers skill (p=0,000), by using Implan for KB acceptor in Inpatient Health Centers Sukabumi, Bandar Lampung, in 2016. The multivariate analisys showed that age was the most dominant variable related to (p=0,000 and OR=6,39).